Digital Transformation in Healthcare Management: A Bibliometric and Systematic Literature Review - Akbar Rafsanjani; Muhammad Qais Rezvani (CV Media Inti Teknologi, 2026)
Background: Digital transformation has become a strategic priority for healthcare organizations, driven by the growing adoption of digital health technologies, telemedicine, artificial intelligence, and health information systems. Despite increasing scholarly attention, the literature remains fragmented across disciplines, limiting a comprehensive understanding of its intellectual structure, dominant themes, and future directions.Aims and Scope of the Paper: Therefore, this study systematically examines the development of digital transformation research in healthcare management using a combined bibliometric and systematic literature review approach.Methods: Data were retrieved from the Scopus database and screened using the PRISMA framework, resulting in 62 publications published between 2016 and 2026. Bibliometric analysis was conducted using VOSviewer to explore publication trends, collaboration networks, citation structures, and thematic relationships, while thematic synthesis was used to identify major research themes and emerging topics.Result: The findings indicate substantial growth in research on digital transformation in healthcare management, particularly after 2022, accompanied by increasing international collaboration and citation activity. Healthcare management, digital health, and telemedicine emerged as the most prominent themes. Keyword co-occurrence analysis identified five major research clusters: Digital Health Transformation, Telemedicine and Remote Healthcare Services, Health Information Systems and Data Governance, Artificial Intelligence and Healthcare Innovation, and Workforce Development, Leadership, and Organizational Readiness. Overlay visualization further highlighted emerging interests in workforce competency, digital leadership, health information management, and data security.Conclusion: This study provides a comprehensive mapping of the intellectual structure of digital transformation research in healthcare management and identifies key research gaps related to workforce readiness, artificial intelligence governance, healthcare cyber security, and sustainable digital transformation strategies. The findings offer valuable insights for researchers, healthcare managers, and policymakers seeking to advance healthcare digitalization initiatives.